2003
DOI: 10.1016/s0021-9924(03)00048-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of four years of exercise, language, and social interventions on Alzheimer discourse

Abstract: This article describes a comprehensive cognitive-linguistic intervention program for mild to moderate Alzheimer's disease (AD) patients that provided communication skills practice in the context of health-enhancing and esteem-building community-based activities: physical fitness training and supervised volunteer work. The interventions were administered by undergraduate students who completed academic work, received faculty supervision, and earned three credits for one semester of participation. Effects of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 40 publications
2
28
0
Order By: Relevance
“…32 Cognitive and emotional benefits of exercise for PWD have been well supported in other studies, including decreased depression and apathy in exercisers compared with nonexercisers. 5,[18][19][20]23,24 Findings from this pilot study are also consistent with the growing body of research describing the effects of CBT on cognitive and behavioral outcomes, including depression. 7,[36][37][38]40 Overall, results from this preliminary study are consistent with findings from previous studies, including the measures used to assess the effects of the multimodal intervention.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…32 Cognitive and emotional benefits of exercise for PWD have been well supported in other studies, including decreased depression and apathy in exercisers compared with nonexercisers. 5,[18][19][20]23,24 Findings from this pilot study are also consistent with the growing body of research describing the effects of CBT on cognitive and behavioral outcomes, including depression. 7,[36][37][38]40 Overall, results from this preliminary study are consistent with findings from previous studies, including the measures used to assess the effects of the multimodal intervention.…”
Section: Discussionsupporting
confidence: 84%
“…22 As persons in the early stages of dementia were the target population for the pilot study, appropriate behavioral outcomes included depression and self-esteem. Studies examining the effects of exercise in PWD showed improvements in depression [23][24][25] and lower rates of depression in exercisers compared with nonexercisers, although sample sizes have tended to be small, <30/group. 26 The type of tested exercise form varied, with home-based aerobic/ endurance activities, strength training, balance and flexibility training being most common.…”
Section: Background Effects Of Exercise On Cognitive Physical and Bmentioning
confidence: 99%
“…Quayhagen and Quayhagen (1989) reported the efficacy of a dyadic cognitive stimulation program, in which patient and caregiver were involved in communication and problem-solving exercises. Cognitive stimulation appeared to be beneficial in numerous studies (Arkin 1992;Quayhagen et al 1995;Arkin 1999;Arkin 2000;Quayhagen and Quayhagen 2001;Mahendra and Arkin 2003;Spector et al 2001;Arkin 2007), also showing that involving spousal caregivers in the cognitive stimulation program (Quayhagen and Quayhagen 1989) and utilizing games (Sobel 2001) lead to significant cognitive improvements.…”
Section: General Enhancement Of Cognitive and Social Functioningmentioning
confidence: 99%
“…Utilization of artistic activities to cope with the psychosocial symptoms encountered in Alzheimer's patients is gaining popularity [1,2]. Some research on Alzheimer's disease has illustrated that multiple therapeutic techniques including music, art, scents of essential oils, massage, touching, object presentation (naming an object displayed by the researcher), and exercise [3][4][5][6][7] can be employed for managing the symptoms.…”
Section: Introductionmentioning
confidence: 99%